Evolution of a comprehensive, orthogonal approach to sequence variant analysis for biotherapeutics. Issue 1 (2nd January 2019) - Lin, T. Jennifer; Beal, Kathryn M.; Brown, Paul W.; DeGruttola, Heather S.; Ly, Mellisa; Wang, Wenge; Chu, Chia H.; Dufield, Robert L.; Casperson, Gerald F.; Carroll, James A.; Friese, Olga V.; Figueroa, Bruno; et al.
ABSTRACT: Amino acid sequence variation in protein therapeutics requires close monitoring during cell line and cell culture process development. A cross-functional team of Pfizer colleagues from the Analytical and Bioprocess Development departments worked closely together for over 6 years to formulate and communicate a practical, reliable sequence variant (SV) testing strategy with state-of-the-art techniques that did not necessitate more resources or lengthen project timelines. The final Pfizer SV screening strategy relies on next-generation sequencing (NGS) and amino acid analysis (AAA) as frontline techniques to identify mammalian cell clones with genetic mutations and recognize cell culture process media/feed conditions that induce misincorporations, respectively. Mass spectrometry (MS)-based techniques had previously been used to monitor secreted therapeutic products for SVs, but we found NGS and AAA to be equally informative, faster, less cumbersome screening approaches. MS resources could then be used for other purposes, such as the in-depth characterization of product quality in the final stages of commercial-ready cell line and culture process development. Once an industry-wide challenge, sequence variation is now routinely monitored and controlled at Pfizer (and other biopharmaceutical companies) through increased awareness, dedicated cross-line efforts, smart comprehensive strategies, and advances in instrumentation/software, resulting in even higher product quality standards for biopharmaceutical products.